PEMBERDAYAAN UMAT LINGKUNGAN STASI POJOK PENGEMBANGAN GUA MARIA PENOLONG ABADI PAROKI SANTO PETRUS DAN PAULUS KLEPU - R. Rubiyatno; Yusef Widya Karsana; A. Joko Siswanto; Fr. Reni Retno Anggraini; Novita Dewi (Universitas Sanata Dharma, 2022)
This Community Service aims to empower people in the POJOK environment in structuring and developing the prayer garden of the Maria Cave, Mother of Eternal Helper (GMPA). Partners involved in this service are volunteers, observers, and donors. The steps in this community service are (1) Conducting discussions with the people who live around the cave location; (2) Assisting the people in arranging the place of prayer to create a comfortable, clean, neat, beautiful, cool, safe, and polite atmosphere; (3) Helping the people to obtain funds to buy sand, cement, bricks in the business of making boreholes and providing RO water; (4) Assisting the people in managing and maintaining the facilities in the location around the Maria Cave; and (5) Assisting the people in serving the visitors to the Cave of Mary who will pray. The result of this service is the implementation of the arrangement of facilities and environments for prayer places, such as water sources, bathrooms, shade trees, and seats. With the support of donors, at this time the Cave of Mary has also been equipped with various adequate prayer facilities, such as a statue of Mary, the Corpus of Jesus, and a candle holder. With the availability of complete prayer facilities and a neat arrangement of the cave environment, now the Maria Cave